Does TQM affect Indonesian food sector production efficiently? - Hendarto, Totok; Haanurat, A. Ifayani; Dhakal, Amrit (CV. Bimbingan Belajar Assyfa, 2023)
Globalisation Parahadi helps each nation adjust its economic policy. Every Haruus destroyer may see the future orientation, and Haru Flexic data in any applicable Kamilan data is a mandate. An integrated quality management system like Total Quality Management (TQM) must be justified to generate high-quality products and services. This study uses qualitative methods literature studies on operational method management to investigate how Total Quality Management (TQM) affects food sector production efficiency in Indonesia. Qualitative and library research approaches to creating scientific articles delays. Google Scholar's literary section or related literary review section over the last ten years 2013-2023 discusses a collection of libraries. It will then bandage prior results or discoveries from Sebi Sebiman's Law on Results or Discoveries. Harzing publishes or finishes all quoted scientific articles from data search data. The delay affects production efficiency and product quality prices. TQM improves manufacturing cost efficiency, especially in food production. This article will explain how operational management uses TQM to cut gift production costs.